PENGARUH KOMPENSASI DEWAN KOMISARIS DAN DEWAN DIREKSI TERHADAP KINERJA MANAJERIAL DENGAN RISIKO BISNIS SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Syoraya, Siti; Januarti, Indira (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the effect of compensation board of commissioners and board of directors to managerial performance with business risk as a moderating variable. Managerial performance is measured using the discrestionary accruals. Independent variables used in this study is compensated board of commissioners and board of directors while the dependent variable is managerial performance. Several previous studies have shown varying results. To obtain valid results, the testing performed on each variable based on the hypothesis constructed. The study population was 148 manufacturing companies listed in Indonesia Stock Exchange. The samples used were selected by purposive sampling method. After reduction with several criteria, 47 companies are identified as samples. Observation period is 2010-2012 years, so the number of samples used is 129 samples. Hypothesis testing is performed by using the Moderated Regression Analysis. The results show that compensation commissioners and the board significant effect on managerial performance and also business risks can be moderate (strengthen) the relationship of managerial compensation to performance.